Sensemaking and Power - Merete Storgaard (Nordic Journal of Comparative and International Education, 2018)
The modernization of governance and the marketization of the Danish public education sector since the 1980s, has resulted in changes both in the constitutive conditions and in the discursive understandings framing the purpose of the public education system for educational leaders, teachers, and social educators working in schools. We know less about how the neoliberal modernization processes affect the schools at a micro-processual sensemaking level and a relational power level. In this analytical perspective, there is a scientific need to understand how these organizing and sensemaking processes are conducted through the discursive construction of power relations in modernized, institutional settings, and how these processes affect the organizational understandings, professional identities and social relations of the members in a high-achieving Danish public school. I investigate leadership from a micro-analytical perspective, as inter-action processes centered around the creation of common understanding and the enactment of policy, and mobilize a theoretical understanding of leadership processes as social sensemaking constructions that are constituted, framed and transformed in a given context of discursive and institutional power. I argue that the members of the organization holding both formal and informal leadership positions construct under-standings through social power struggles in ambiguous and contradictory discursive orders. Further, these struggles create new power relations and democratic forms of leadership within a hidden power structure of a high-achieving Danish school owing to governance transitions in the Danish public education sector.